Axiological aspects of upbringing - Zofia Remiszewska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The article presents issues concerning the axiological aspect of upbringing, it is also a search for the answers to the question: How to raise a young man so that he could move in the axiological space, and could discover, create and accept the values during a search of his place in the world? I believe that in order to raise a young man, so he would live according to the universal values, it should be ensured that he would be able to learn the objective recognition and respect the values, that he would be able to arouse his interest in a valuable living. In this article, I note that axiological dimension of human activity is refocusing on the "lower" values (hedonistic, utilitarian, vital, prestige). The dimension of moral values is weakening (courage, justice, goodness), positive values penetrate each other with negative values. What matters is the individualization, responsibility for oneself, people lean toward material values, which replaced the values of the spiritual dimension. The dialogue between a young man and educators, teachers and parents is necessary in order to build among young people axiological structure of internal development, although it is difficult to compete with hedonistic values, when the consumer dimension of life becomes widespread. In this dialogue - referring to the aspects of personality and humanistic psychology and also using the elements of existential psychology - maybe it will be easier to convince young people to treat the world of consumption critically. It is not about complete cancellation of the benefits of the modern world, but about learning to recognize its dangers and how to cleverly move in it.